THE INFLUENCE OF INCENTIVES, QUALITY, AND PRODUCT AVAILABILITY ON ATTITUDE TOWARD PURCHASE DECISION OF BATTERY ELECTRIC VEHICLE AT THE GREATER JAKARTA - Sonhaji, Sonhaji; Ong, Leonnard (Bina Nusantara University, 2024)
Transport and mobility have significant contributions to the emissions in urban cities in Indonesia. The Indonesian government has supported the adoption of electric vehicles (EVs) as part of the commitment to zero emissions by 2060. According to The Association of Indonesia Automotive Industries (GAIKINDO), in 2022 the electric vehicle contributes 1.49% of the total domestic passenger car sales in Indonesia. This EV population was too small compared to what the government targeted for the adoption of EVs. This study aims to analyze the influence of government incentives, product quality, and product availability on consumer’s attitudes toward purchase decisions of battery electric vehicles (BEV). A sample of 149 respondents, who have a driving license, live in the greater area of Jakarta were collected through a questionnaire-based primary data. Through a rigorous procedure of structural equation modeling (Smart-PLS), it is found that variables of government incentives and product quality have no significant effect on consumer purchase decision for BEVs. Product availability and attitude variable has positive and significant effect on consumer purchase decision for BEVs. Moreover, the product availability variable is imperative since it is found to be the most significant variable construct. Thus, as the managerial implication, BEV dealer and manufacturer could consider the availability of various choices of electric cars with the price and driving range capabilities. Future research is recommended to cover all types of EVs, collect wider respondents on different areas and also explore different variables that influence EV customer purchase decision.